Pendidikan Anak dalam Keluarga Perempuan Pengupas Kulit Kerang di Lingkungan 2 Benteng Sungai Belawan Bahari - Firmansyah, Wira; Rulyani, Ayu; Malau, Waston; Naibaho, Zanrison; Nanta, Arimbi Aulia; Januardani, Sri Melani; Dhevany, Dhevany (Jurnal Ilmiah Dikdaya, 2024)
Education is one of the main pillars in building the quality of life of individuals and communities. This study aims toexamine in depth the education of children in the families of women shellers in the slum and identify the factors that influencetheir low access to education. This study is a descriptive qualitative research, this method is conducted to understand the impactof poverty and parenting on children's education in the families of women shellers in Benteng Sungai Belawan Bahari. The resultsshowed that children of women shellers in Benteng Sungai Belawan Bahari face significant challenges in education due to poorsocial and economic conditions. Children prefer to work to help their families rather than go to school, showing the differencebetween the educational conditions of children of shellers and children from Tekong families. Without effective interventions,this cycle of poverty will continue, hindering equitable access to education and social transformation